Latrinae : Roman toilets in the northwestern provinces of the Roman Empire - Hoss, Stefanie, (Archaeopress Roman archaeology ;, 2018)
This volume presents a selection of papers and case studies on toilets and toilet-use in the Northwestern provinces of the Roman Empire. It is hoped this volume will promote and stimulate further research in this interesting research topic.